Language separateness: A normative framework in studies of language alternation - Gafaranga, Joseph (Sociolinguistic Studies, 2000)
In this paper, I argue that, for a 'faithful' account of the orderliness of language alternation among bilingual speakers, an attitude of indifference must be adopted inapproaching the data. More specifically, I argue that bilingual speakers cannot be assumed to be 'normatively' speaking either language A or language B. They could also have adopted the use of both languages as the medium (Gafaranga, 1998, 1999, 2000). To demonstrate the need for such an attitude, the paper looks at four of the most influential accounts of language alternation, namely the work of Fishman, Gumperz, Myers-Scotton and Auer. It shows that these accounts fail to capture the orderliness of language alternation because they approach bilingual conversations, not with an attitude of indifference, but from a normative framework whereby every instance of language alternation is defined in terms of language separateness.